Next steps for climate change mitigation in agriculture - Wollenberg, Eva Karoline; Negra, Christine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Agriculture can contribute significantly to climate change mitigation, but more action is needed to identify appropriate implementation mechanisms, technical guidelines, policies and sources of finance to improve readiness and capacity building.